Delayed response of epididymal sperm characteristics and testicular oxidative stress following EGME exposure: Ameliorating potential of Withania somnifera root extract - Praveen Kumar, Poonam Singh (Journal of Applied Pharmaceutical Science, 2018)
Swiss strain male mice were administered orally with ethylene glycol monomethyl ether (EGME) for 6 and 10 days and studied the epididymal sperm characteristics and testicular oxidative stress 24 hours after each duration. Withdrawal study on the same parameters was carried out 20 and 45 days after the mice received EGME for 10 consecutive days. Efficacy of Withania somnifera (Ws) root extract was also studied in the mice received EGME for 10 days only, followed by oral administration of WS, from 11th day to 30th day. Treatment with Ws root extract was then terminated and studied the effects on 31st day. EGME treatment for 6 and 10 consecutive days did not cause significant alterations in the percentage of motile, viable, count and abnormal spermatozoa in the epididymis as well as the oxidative stress in the testis. However significant reductions were noted in these sperm indices with a significant increase in abnormal spermatozoa in the epididymis of 20 days EGME-withdrawal group. Oxidative stress in the testis of the mice of the same group was also elevated as evidenced by significant reductions in the activities of antioxidant enzymes (SOD, catalase and GPX) and increase in lipid peroxidation. Forty five days after withdrawal of the treatment, as well as supplementation with Ws for 20 days in 10 days EGME-treated mice resulted in significant reinstatement in these parameters. The study suggested that the toxicity of EGME noticed during early treatment withdrawal period, may be prevented by Ws root extract therapy.
Keywords: Ethylene glycol monomethyl ether, Withania somnifera, Epididymis, Sperm, oxida¬tive stress.